Exploring the Acetone Evaporation and Airborne Neurotoxicity Bioassay against Adult Mosquito in the Enclosed Environment of Peet Grady Chamber - Jahangir Kamaldin; Zairi Jaal (Jurnal Kimia Terapan Indonesia, 2018)
Mosquito has comprehensive and sensitive olfactory neuro-sensory located at antenna utilized for detecting airborne organic compounds in search of blood host. Mosquito is also known to have similar neurotransmitters function with human at neural synapses e.g. acetylcholinesterase, esterases and oxidases enzymes. Thus, there is potential use mosquito in predicting neurotoxicity of exogenic volatile organic compounds (VOC) e.g. manufactured acetone. Hence, the study evaluates the suitability to conduct bioassay of VOC neurotoxicity against mosquito in Peet Grady chamber that is commonly used for insecticidal bioassay. Acetone as the representative of VOC is easily evaporized at laboratory temperature of 26 to 29 Â°C without heating. The acetone evaporation profile on liquid surface and porous solid surface under the Peet Grady chamber is studied to ascertain the consistency of vaporization rate with homogenized distribution. The study showed the acetone has shown consistent vaporization rate of 23 mg/min from liquid surface and 116.3 mg/min from porous surface (filter paper) without heating, in a linear regression of very high positive correlation (r = 1.000) between time and mass of acetone vaporized. However, the non-homogenized distribution of acetone vapours in the Peet Grady chamber directly affected the accuracy to elucidate the neurotoxicity bioassay against mosquito in term of mosquito knockdown. The study suggests the positioning of mosquitoes in the Peet Grady chamber should be lower than the point of acetone vaporization, whereby the mosquitoes are knockdown by acetone vapours within the 20th minute upon reaching concentration of 170.3 to 196.1 ppm.